2019
DOI: 10.1002/ajmg.a.61104
|View full text |Cite
|
Sign up to set email alerts
|

Improved clinical outcome following liver transplant in patients with ethylmalonic encephalopathy

Abstract: Ethylmalonic encephalopathy (EE) is a rapidly progressive autosomal recessive mitochondrial disease caused by biallelic pathogenic variants in the ETHE1 gene that encodes the mitochondrial sulfur dioxygenase. It is characterized by neurodevelopmental delay and regression, pyramidal and extrapyramidal signs, recurrent petechiae, chronic diarrhea, and orthostatic acrocyanosis. Laboratory findings include elevated serum levels of lactate and C4-C5 acylcarnitines, and elevated urinary excretion of ethylmalonic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 17 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…LT rapidly normalized serum levels of toxic nucleosides in a 25-year-old MNGIE patient, and his conditions were stable after 400 days of follow-up [ 395 ]. LT also resulted in an effective option to treat ethylmalonic encephalopathy due to mutation in ETHE1 gene [ 396 , 397 ], since the replaced organ can substitute the deficient ETHE1 enzyme and clear the toxic H 2 S that accumulate in this disorder, constituting a feasible therapeutic option in patients. Patients showed progressive improvement of the neurological functions and normalization or amelioration of the biochemical abnormalities [ 396 , 397 ].…”
Section: Precision Medicine Approaches For Pmd Caused By Nuclear Dmentioning
confidence: 99%
See 1 more Smart Citation
“…LT rapidly normalized serum levels of toxic nucleosides in a 25-year-old MNGIE patient, and his conditions were stable after 400 days of follow-up [ 395 ]. LT also resulted in an effective option to treat ethylmalonic encephalopathy due to mutation in ETHE1 gene [ 396 , 397 ], since the replaced organ can substitute the deficient ETHE1 enzyme and clear the toxic H 2 S that accumulate in this disorder, constituting a feasible therapeutic option in patients. Patients showed progressive improvement of the neurological functions and normalization or amelioration of the biochemical abnormalities [ 396 , 397 ].…”
Section: Precision Medicine Approaches For Pmd Caused By Nuclear Dmentioning
confidence: 99%
“…LT also resulted in an effective option to treat ethylmalonic encephalopathy due to mutation in ETHE1 gene [ 396 , 397 ], since the replaced organ can substitute the deficient ETHE1 enzyme and clear the toxic H 2 S that accumulate in this disorder, constituting a feasible therapeutic option in patients. Patients showed progressive improvement of the neurological functions and normalization or amelioration of the biochemical abnormalities [ 396 , 397 ]. However, the decision to perform LT remains difficult because neurological manifestations may worsen despite their absence before the transplant [ 398 ].…”
Section: Precision Medicine Approaches For Pmd Caused By Nuclear Dmentioning
confidence: 99%
“…Dual treatment caused marked improvement in 5 EE patients, almost without side effects as follows: body weight increased; diarrhea occurred less frequently; petechiae, acrocyanosis and seizures decreased or disappeared; hypotonia showed marked improvement; and plasma EMA significantly decreased in all 5 affected children. In addition, liver transplantation is considered as a viable therapeutic option for EE (Dionisi-Vici et al, 2016;Tam et al, 2019). Although only 3 EE patients achieved psychomotor developmental improvement and marked reversion of biochemical abnormalities after liver transplantation, their outcomes support the promising approach as a standard treatment for EE.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, untargeted metabolomics profiling (Kennedy et al, ; Miller et al, ) performed on Patient 1 revealed elevated lactate, fumarate and glutarate, which indicate perturbation in energy metabolism secondary to mitochondrial dysfunction further providing functional evidence for the pathogenicity of the variant identified in COX4I1 . Evidence of mitochondrial dysfunction by the use of untargeted metabolomics analysis in CSF and plasma may provide functional validation for variants of unknown significance observed in nuclear genes associated with mitochondrial disease, providing semi‐quantitative values for TCA cycle intermediates and altered lipid metabolism as a consequence of abnormal mitochondrial function (Esterhuizen, Van Der Westhuizen, & Louw, ; Shayota et al, ; Tam et al, ).…”
Section: Discussionmentioning
confidence: 99%